Investigation of turbulent flow in a Schwarz Diamond monolith using MRI and CFD - Clarke, Daniel A. ; 0000-0001-7668-2472; Coe, Michael J.; Galvosas, Petrik; Holland, Daniel J. (Chemical Engineering Journal, 2025)
Particle packings are widely used in process applications, yet often have poor flow distribution due to random channel geometries. Regular channels can now be realised using 3D-printing, where tuneable channel morphology also offers the possibility of promoting vortices and fluctuating motion to enhance heat and mass transfer. Detailed visualisation experiments are required to understand hydrodynamics and to validate numerical simulations. In this article, magnetic resonance velocimetry experiments were performed using a single point imaging sampling scheme. This technique enabled quantitatively accurate measurements within ±5% of the mean axial velocity for Reynolds numbers from 340 to 1500. Measurements of the velocity variance indicated the presence of free shear instabilities that enhance fluid mixing in the pore centres. We found that unsteady computational fluid dynamics using detached eddy simulation could accurately replicate the mean and variance of the velocity field measured by experiments. These measurements can provide insight into effective design and operation of 3D-printed reactors and heat exchangers.
Keywords: Magnetic resonance imaging; Triply periodic minimal surface; Turbulent flow